2021
DOI: 10.1080/19317611.2021.1947931
|View full text |Cite
|
Sign up to set email alerts
|

Non-consensual and Consensual Non-monogamy in Norway

Abstract: The paper sets out to study Norwegians' experiences of non-monogamy. Data were collected by questionnaires in a web sample of 4160 Norwegians (18-89 years). 26.3% of men and 17.8% of women reported that they ever had non-consensual non-monogamy. Consensual non-monogamy was reported by 3%. Compared to participants with no or nonconsensual experience, consensual non-monogamy was highly related to relationship intimacy and positive sexual attitudes toward sex and sexuality. At the most recent extradyadic event, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Though most studies ( n = 28) compared monogamous partnerships to CNM partnerships, others ( n = 11) compared concurrent CNM partnerships (e.g., comparing primary partnerships to secondary partnerships; Balzarini et al, 2017; Balzarini, Dharma, Kohut, Campbell, et al, 2019), while others ( n = 8) compared different types of CNM partnerships (e.g., polyamorous relationships to open relationships to swingers; Conley & Piemonte, 2021). A few studies ( n = 6) compared consensually non‐monogamous relationships to non ‐consensually non‐monogamous relationships (i.e., infidelity) (Levine et al, 2018; Rodrigues et al, 2019; Rodrigues, Lopes, Dawson, et al, 2021; Træen & Thuen, 2021). We present the findings of these studies below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though most studies ( n = 28) compared monogamous partnerships to CNM partnerships, others ( n = 11) compared concurrent CNM partnerships (e.g., comparing primary partnerships to secondary partnerships; Balzarini et al, 2017; Balzarini, Dharma, Kohut, Campbell, et al, 2019), while others ( n = 8) compared different types of CNM partnerships (e.g., polyamorous relationships to open relationships to swingers; Conley & Piemonte, 2021). A few studies ( n = 6) compared consensually non‐monogamous relationships to non ‐consensually non‐monogamous relationships (i.e., infidelity) (Levine et al, 2018; Rodrigues et al, 2019; Rodrigues, Lopes, Dawson, et al, 2021; Træen & Thuen, 2021). We present the findings of these studies below.…”
Section: Resultsmentioning
confidence: 99%
“…Studies comparing people in CNM relationships to those who have engaged in non ‐consensually non‐monogamous relationships (NCNM, or infidelity) found that those in CNM relationships reported greater intimacy with their primary partners and more accepting attitudes toward sex and sexuality than those who engaged in NCNM (Træen & Thuen, 2021). Individuals in CNM relationships were found to use condoms more effectively than those engaging in infidelity (Conley et al, 2013; Rodrigues et al, 2019) though contrary findings were reported in one study (Træen & Thuen, 2021). Those in CNM relationships also reported higher sexual satisfaction compared to those engaging in infidelity (Rodrigues, Lopes, & Huic, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…This may hinder the generalizability of the results. A more detailed description of this has been outlined elsewhere (Traeen et al, 2021a, b;Traeen & Thuen, 2021;. Another limitation is the single question measure of satisfaction with singlehood, as well as satisfaction with their sexual life/current level of sexual activity.…”
Section: Limitationsmentioning
confidence: 99%
“…Other sample characteristics are presented elsewhere . This study is part of a larger project concerning a wide range of non-BDSM-related aspects of sexuality and other articles from this larger project have been published (Fisher & Traeen, 2021;Koletić et al, 2021;Traeen & Thuen, 2021).…”
Section: Participantsmentioning
confidence: 99%